Low-ILUC-risk rapeseed biodiesel: potential and indirect GHG emission effects in Eastern Romania. Issue 2 (7th February 2021) - Brinkman, Marnix L. J.; van der Hilst, Floor; Faaij, André P. C.; Wicke, Birka
ABSTRACT: Indirect land-use change (ILUC) can have a severe impact on the greenhouse gas (GHG) balance of biofuels. Mitigating ILUC risk is important to avoid additional GHG emissions compared to fossil fuels. This is possible by making surplus land available through land demand reduction and using this for low-ILUC-risk biodiesel production. For a case study in Eastern Romania, we calculated the rapeseed biodiesel potential and the GHG emissions of four measures to make surplus land available in 2020. Four scenarios varying in assumptions on productivity and sustainability in the agricultural sector show the variation in the potential of these measures. We find that using surplus land to produce low-ILUC-risk rapeseed biodiesel has a potential of 3-64 PJ, 1-28% of the projected Romanian transport diesel consumption. The main contribution to this potential comes from yield improvements in crop and livestock production. Average GHG emissions of the ILUC mitigation measures are -11 to 22 g CO2 -eq MJ −1 (maximum total lifecycle emissions are 34 g CO2 -eq MJ −1 ; 60% reduction from fossil fuel reference). This means ILUC mitigation is possible without necessarily missing the GHG emission reduction target, provided that the entire agricultural sector is sustainably intensified, going beyond a focus on biofuel production alone.